Local wisdom values of merti desa: resource for learning social studies in Boja Village, Kendal - Agriawan, Gilang; Masrukhi, Masrukhi; Arsal, Thriwaty (Universitas Negeri Semarang, 2023)
The Merti Desa tradition is local wisdom carried out by the people of Boja Village. Behind the implementation of the Merti Desa tradition are values and deep meanings for the community. However, in this modern era, more and more people need to learn the values contained in the Merti Desa. The purpose of this study is to examine the values of local wisdom of the Merti Desa tradition and analyze the application of the Merti Desa tradition and the obstacles that arise in the application of the Merti Desa tradition as a source of social studies learning. This study used qualitative methods. Data were collected using interviews and data analysis using interactive models. The results showed that there are values in the Merti Desa tradition, namely religious, mutual aid, and cultural values. The strategy teachers use in its application is through learning media in the form of photos and videos and direct observation in the field. The obstacles that arise are more technical in the form of limited time in delivering material, mastery of the material, and limitations of facilities and infrastructure.